Strategi Peningkatan Keterlibatan Pasien dan Keluarga dalam Advance Care Planning di Unit Gawat Darurat - Birry Assidiqy; Ai Rahmawati; Heni Nurakilah (Universitas Malahayati Lampung, 2025)
ABSTRACT A visit to the Emergency Department (ER) provides an opportunity to empower patients and families to discuss advanced care planning (ACP). However, various obstacles are felt when implementing ACP in the ER. Lack of patient and family participation in ACP formulation is a significant obstacle to overcome. This review aims to identify strategies or interventions that can increase the participation and involvement of patients and families in formulating ACP in the ED. This study used a narrative review by identifying articles from three databases: Pubmed, EBSCOhost: Medline Ultimate, ScienceDirect, and one Google Scholar search engine. The keywords used were “chronic disease OR chronic condition” AND “advance care planning OR advance directive” AND “emergency room OR emergency unit OR emergency context”. The articles analyzed underwent a selection stage based on inclusion and exclusion criteria and were analyzed thematically and qualitatively. A total of seven studies were analyzed in this review and found to include a brief negotiated interview, ACP toolkit, ACP video decision support tool, and remote ACP with a goals-of-care approach. Conclusion: This review concludes that the successful strategies identified in this review can help health workers increase the participation and involvement of patients and families in the ACP formulation process in the ER. Keywords: Advance Care Planning, Emergency Room, Family Participaton and Engagement. ABSTRAK Kunjungan ke Unit Gawat Darurat (UGD) memberikan kesempatan untuk memberdayakan pasien dan keluarga untuk mendiskusikan advance care planning (ACP). Namun, berbagai macam hambatan yang dirasakan dalam pelaksanaan ACP di UGD. Kurangnya partisipasi pasien dan keluarga dalam perumusan ACP menjadi salah satu hambatan yang penting untuk diselesaikan. Review ini bertujuan untuk mengidentifikasi strategi atau intervensi yang dapat meningkatkan partisipasi dan keterlibatan pasien dan keluarga dalam perumusan ACP di UGD. Studi ini menggunakan narrative review dengan mengidentifikasi artikel dari tiga databases seperti Pubmed, EBSCOhost: Medline Ultimate, dan Sciencedirect serta satu search engine Google Scholar. Kata kunci yang digunakan adalah “chronic disease OR chronic condition” AND “advance care planning OR advance directive” AND “emergency room OR emergency unit OR emergency context”. Artikel yang dianalisis sudah melalui tahap seleksi berdasarkan kriteria inklusi dan eksklusi serta dianalisis secara tematis dan kualitatif. Sebanyak tujuh studi yang dianalisis pada review ini dan diapatkan meliputi: Brief negotiated interview, ACP toolkit, ACP video decision support tool, dan remote ACP dengan pendekatan goals of care. Review ini menyimpulkan bahwa strategi-strategi yang berhasil teridentifikasi pada review ini dapat membantu petugas kesehatan untuk meningkatkan partisipasi dan keterlibatan pasien serta keluarga dalam proses perumusan ACP di UGD. Kata Kunci: Advance Care Planning, Partisipasi dan Keterlibatan Keluarga, Unit Gawat Darurat.